2017
DOI: 10.4309/jgi.2016.34.4
|View full text |Cite
|
Sign up to set email alerts
|

Gambling Behaviour and Motivation in British Older Adult Populations: A Grounded Theoretical Framework

Abstract: Gambling participation among older adults aged 65 and above has increased in Great Britain. However, there is limited research and therefore understanding about cognitive and behavioural patterns of gambling for this demographic. The objective of this study is to develop a substantive framework that represents the gambling behaviour of older adults in Great Britain, with specific reference to motivational factors affecting behaviour. A systematic grounded theory approach (Strauss & Corbin, 1998) was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 52 publications
1
18
0
Order By: Relevance
“…The high prevalence of participants who reported gambling behaviour (around 72 per cent of men and 60 per cent of women) is consistent with previous research studies, which show that gambling is a common leisure activity among elderly people in developed countries (Alberghetti and Collins, 2015; Pattinson and Parke, 2016; Subramaniam et al ., 2017 b ). The higher preference of non-strategic gambling was also an expected result, confirming that elderly people usually select simple games (Black et al ., 2017; Granero et al ., 2020; Jiménez-Murcia et al ., 2020).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The high prevalence of participants who reported gambling behaviour (around 72 per cent of men and 60 per cent of women) is consistent with previous research studies, which show that gambling is a common leisure activity among elderly people in developed countries (Alberghetti and Collins, 2015; Pattinson and Parke, 2016; Subramaniam et al ., 2017 b ). The higher preference of non-strategic gambling was also an expected result, confirming that elderly people usually select simple games (Black et al ., 2017; Granero et al ., 2020; Jiménez-Murcia et al ., 2020).…”
Section: Discussionsupporting
confidence: 91%
“…This situation is especially problematic among elderly people, since it has been observed that older adults with a GD often experience higher levels of psychological distress and/or comorbidity compared with younger adults (van der Maas et al ., 2017; Parke et al ., 2018). Unlike younger gamblers, who usually report looking for action and excitement as a primary motivation for gambling (Armstrong et al ., 2020), many older people use gambling as an escape, and seniors with the greatest need for that escape are those with previous physical and/or psychological disease (who are precisely the most vulnerable to developing gambling problems) (Tira et al ., 2014; Medeiros et al ., 2015; Subramaniam et al ., 2015; Pattinson and Parke, 2016). People who have recently lost their partner, or even those who have retired from work, are at risk of suffering from anxiety or depression, and they can find an opportunity to cope with distress in gambling and in the use of comorbid substances (Botterill et al ., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…As noted previously by Alberghetti and Collins ( 2015 ), this approach is already engaged in by several clinical services specific to older adults, such as the Addiction Services of Thames Valley (UK), whose volunteers facilitate social events and interaction across peers, as a direct replacement for gambling. It appears appropriate to encourage clinical and community services to advocate for the creation and facilitation of opportunities for older adults to engage in social interaction in safe and stimulating environments because currently, there appears to be insufficient opportunities available ( Pattinson & Parke, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several core motivations for gambling might be operative in older adult populations. Recent increases in the availability of gambling products and services (including online gambling), combined with age-related physical deterioration, means that gambling may represent one of the few leisure pursuits that are available and highly accessible to older adults ( Alberghetti & Collins, 2015 ; Erickson, Molina, Ladd, Pietrzak, & Petry, 2005 ; Pattinson & Parke, 2016 ; Pietrzak & Petry, 2006 ). For some individuals, old age is associated with retirement from employment and declining social networks and purpose in life ( Alberghetti & Collins, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation